2016
DOI: 10.15252/msb.20166998
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial persistence is an active σ S stress response to metabolic flux limitation

Abstract: While persisters are a health threat due to their transient antibiotic tolerance, little is known about their phenotype and what actually causes persistence. Using a new method for persister generation and high‐throughput methods, we comprehensively mapped the molecular phenotype of Escherichia coli during the entry and in the state of persistence in nutrient‐rich conditions. The persister proteome is characterized by σS‐mediated stress response and a shift to catabolism, a proteome that starved cells tried to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
171
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(193 citation statements)
references
References 60 publications
(84 reference statements)
12
171
0
3
Order By: Relevance
“…Since class 9 strains and the reconstructed rssB strain both show resistance to cell wall inhibitors and other stresses (AZT, CBPC, TET), our results indicate a trade-off between these stresses and metabolic inhibitors. It has been reported that while E. coli strains with higher rpoS levels show increased resistance to several external stresses (Radzikowski et al, 2016), they also show decreased carbon source availabilities and poor competitiveness for low concentrations of nutrients due to the competition between RpoS and the housekeeping sigma factor RpoD (sigma 70) (Ferenci, 2005). Because RssB facilitates the degradation of RpoS, the collateral sensitivities to several metabolic inhibitors in class 9 evolved strains could also be caused by the sigma factor competition.…”
Section: Quantification Of Novel Collateral Sensitivitiesmentioning
confidence: 99%
“…Since class 9 strains and the reconstructed rssB strain both show resistance to cell wall inhibitors and other stresses (AZT, CBPC, TET), our results indicate a trade-off between these stresses and metabolic inhibitors. It has been reported that while E. coli strains with higher rpoS levels show increased resistance to several external stresses (Radzikowski et al, 2016), they also show decreased carbon source availabilities and poor competitiveness for low concentrations of nutrients due to the competition between RpoS and the housekeeping sigma factor RpoD (sigma 70) (Ferenci, 2005). Because RssB facilitates the degradation of RpoS, the collateral sensitivities to several metabolic inhibitors in class 9 evolved strains could also be caused by the sigma factor competition.…”
Section: Quantification Of Novel Collateral Sensitivitiesmentioning
confidence: 99%
“…For instance, pre-treatment with hydrogen peroxide can protect against multiple bactericidal antibiotics by priming oxidative stress responses [33], and nutrient starvation can induce phenotypically tolerant ‘persister’ cells by activating ppGpp and the stringent response [66,67]. Several recent studies demonstrate how environmental factors may alter antibiotic efficacy, providing additional insight into antibiotic lethality (Figure 2).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…OxidizeME represents another step in this direction. There is increasing recognition that microbial stress response plays an important role in infectious disease and antibiotic tolerance [7,8]. Stress-ME models (FoldME, OxidizeME, etc.)…”
Section: Discussionmentioning
confidence: 99%